Dynamics of Inflation and Economic Stability in Facing Global Uncertainty - Salamah Utami (PT. AVID MEDIA INDONESIA, 2026)
Global uncertainty has significantly transformed inflation dynamics, making inflation more volatile and less predictable, thereby challenging economic stability. This study aims to analyze the dynamics of inflation and their impact on economic stability in the context of global uncertainty, emphasizing the mediating role of inflation uncertainty. This research employs a qualitative approach with a descriptive-analytical design based on a systematic literature review of recent empirical studies published between 2021 and 2025. Data were collected through documentation techniques from reputable international journals and institutional reports, and analyzed using qualitative content analysis, thematic categorization, and conceptual synthesis. The findings reveal that economic policy uncertainty, geopolitical risks, and energy price shocks are the primary drivers of inflation volatility, while inflation uncertainty plays a crucial role in transmitting global shocks to macroeconomic instability. These factors collectively weaken economic performance by reducing investment, consumption, and employment. The discussion highlights that the impact of uncertainty is asymmetric, with developing countries being more vulnerable due to structural and institutional limitations. Furthermore, effective policy responses such as credible communication, inflation targeting, and fiscal-monetary coordination are essential in mitigating these adverse effects. In conclusion, maintaining economic stability in an era of global uncertainty requires not only controlling inflation but also managing uncertainty through integrated and adaptive policy strategies.